Emerging models of patchwork capitalism in Central and Eastern Europe: Empirical results of subspace clustering - Ryszard Rapacki; Adam Czerniak (International Journal of Management and Economics, 2018)
The main aim of this paper was to shed a new empirical light on the nature and most salient features of the evolving postcommunist capitalism in 11 Central and Eastern European (CEE11) countries against the backdrop of Western European models of capitalism. The research approach capitalizes on the conceptual framework put forward by Amable [2003, The diversity of modern capitalism, Oxford University Press, Oxford] , i.e., it seeks to identify the current clusters or models of capitalism in 25 European Union (EU) countries in six institutional areas. However, in contrast to the original Amable's methodology, the subspace clustering method was used, what allowed to take into account a vast set of 132 institutional measures and to analyze their change between 2005 and 2014. The main finding is that CEE11 countries developed their own distinct model of capitalism dubbed "patchwork capitalism." In all but two areas, i.e., product market competition and financial intermediation, postcommunist countries form their own institutional clusters that are substantially different from those observed in Western EU countries. In addition, the paper shows that each CEE11 country followed its own distinct vector of change, which eventually led to a unique patchwork of institutions. Yet, the institutional variance within the region is smaller than the difference between CEE11 countries and other country clusters in the EU.
Keywords: O17; P16; P51; C38; 650; Comparative Capitalism; Models of Capitalism; Institutions; Institutional Complementarity; Patchwork Capitalism; Subspace Clustering